Choosing the Correct Currency Anchor for a Small Economy : The Case of Nepal - Beadle, Sibel (IMF Working Papers; Working Paper, 2004)
This paper uses the Sjaastad model to estimate the optimal currency area for the Nepalese rupee and concludes that, currently, Nepal may be reasonably well off with its peg to the Indian rupee. As its economy opens and its trade base and trading partners expand, it may want to reevaluate whether moving toward an exchange rate basket including the U.S. dollar may be a better policy choice. The regression results indicate that, currently, the prices of imported goods in Nepal are solely influenced by India, suggesting that with the peg to the Indian rupee, Nepal can isolate the import side of its economy completely from external shocks. On the export side, the regression results indicate that Nepalese export prices seem, to a large extent, to be influenced by U.S. prices. However, the export price index had to be constructed, and the construction methodology is likely to entail an overestimation of the impact of the U.S. dollar.